2006
DOI: 10.1159/000092795
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Risk of Stroke in Patients with a Hospital Diagnosis of Nonvalvular Atrial Fibrillation: National Cohort Study in Denmark, 1980–2002

Abstract: Aim: We examined trends in incidence of stroke of any nature (ischemic and/or hemorrhagic) in subjects with a hospital diagnosis of nonvalvular atrial fibrillation or flutter in Denmark from 1980 to 2002 by sex, age and conditions of comorbidity. Methods: We identified all individuals, aged 40–89 years, with an incident hospital diagnosis of atrial fibrillation or flutter and no history of stroke or heart valve disease in the Danish National Registry of Patients, and subjects were followed in the Danish Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…Previously reported incidence rates of stroke are in the same range as in our study but did not include detailed information on VKA use from newly diagnosed patients with AF of the recent years 13 14. For ischaemic stroke, the incidence rate reported by Go et al 15 in patients taking warfarin and for patients not taking warfarin is in agreement with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Previously reported incidence rates of stroke are in the same range as in our study but did not include detailed information on VKA use from newly diagnosed patients with AF of the recent years 13 14. For ischaemic stroke, the incidence rate reported by Go et al 15 in patients taking warfarin and for patients not taking warfarin is in agreement with our study.…”
Section: Discussionsupporting
confidence: 91%
“…This decrease in patients >85 years of age, was probably related to competing mortality risks, which showed a sharp increase in incidence rate in both men and women with AF >85 years of age. The rates of ischemic stroke in the present study are comparable to those reported in the Loire Valley Atrial Fibrillation Project 44 in Denmark, 45 in the United States, 46 and in Canada 47 but are somewhat lower than those reported in other studies mostly from Europe. 38,48 Several factors may explain our lower reported rates.…”
Section: Discussionsupporting
confidence: 82%
“…In a similarly organized cohort study of AF, the hospital diagnosis for AF was well validated; evidence for AF was found in 99%. 29 Another possible limitation is the underreporting of some comorbidities, especially hypertension.…”
Section: Selection Biasmentioning
confidence: 99%